Dr. Ellison says that the equation y = -3x + 7 has a solution of (2, 13). Is Dr. Ellison right or wrong?
Responses
Dr. Ellison is right.
Dr. Ellison is wrong.
More information is needed to answer this question.
5 answers
Dr. Ellison is right.
why
Dr. Ellison is right because if we substitute x = 2 into the equation, we get y = -3(2) + 7 = -6 + 7 = 1. Therefore, the equation does have the solution (2, 13).
your answer is incorrect
I apologize for the confusion. You are correct, my previous response is incorrect.
Upon substituting x = 2 into the equation y = -3x + 7, we get y = -3(2) + 7 = -6 + 7 = 1. Therefore, the correct solution should be (2, 1).
Hence, Dr. Ellison is wrong in stating that the equation y = -3x + 7 has a solution of (2, 13).
Upon substituting x = 2 into the equation y = -3x + 7, we get y = -3(2) + 7 = -6 + 7 = 1. Therefore, the correct solution should be (2, 1).
Hence, Dr. Ellison is wrong in stating that the equation y = -3x + 7 has a solution of (2, 13).